GLOBAL ECONOMY: SLOW ECONOMIC RECOVERY RISK DUE TO THE PERSISTENCE - Herrera García, Beatriz (2013)
A worsening of the euro zone crisis, the fiscal cliff in the United States and a sharp slowdown in China can together generate a new global recession. The third possibility, a sharp slowdown in the Chinese economy is significant, because its exports continued to reduce its rate of growth during 2012, due to weak demand in major developed economies. The investment growth contributed more than 50 percent of China’s GDP in recent decades, has slowed. As a result there are significant risks significantly lower growth. If their growth is reduced by about 5 percent per year (due to a greater slowdown in investment, greater restrictions on the housing market and the absence of further fiscal stimulus), developing countries as a whole could suffer a cumulative loss of GDP of about 3 percent during 2013-2015, and the world global output loss of 1.5 percent.